Estudo das propriedades vibracionais e estruturais do ácido Gama-aminobutírico em condições extremas de temperatura e de pressão - Silva, Cícero Moézio (2017)
This work shows a study of the vibrational properties of γ-aminobutyric acid crystals under extreme conditions. The vibrational normal modes of the crystal were assigned at ambient conditions in the spectral range 20-3000 cm−1. Raman spectra were investigated for temperatures between 20 and 440 K; X-ray diffractogram and Rietveld analysis were obtained for crystal in the temperature range 110-440 K. From this analysis it was possible to infer that above room temperature the original monoclinic P21/c is verified. For low temperatures it was noted that the a parameter increasing anomalously with cooling, while the b and c parameters as well as the volume of the unit cell diminishes. Additionally, it was observed change in the dimension versus pressure curves of the b and c parameters at 220 K. The anomaly in the c-axis was associated with small changes in the hydrogen bonds along the (001) direction. Also, pressure Raman meassurements were performed on γ-aminobutyric acid crystal up to 7.1 GPa. Three different phase transition (at 0.1, 2.0 an 4.0 GPa) during the compression run were observed. Changes in the Raman spectral were interpreted mainly as change of molecular confomations. In the phase transition occurring at 4.0 GPa it was observed modification in the CC-stretching, CH2-bending, torsion of NH+ 3 and rocking of NH+ 3 . These two last points suggest modifications in the hydrogen bond network linking the various molecules into the unit cell. It was observed no cracking of the sample during the compression - decompression run, suggesting a soft conformational change. No indication of pressure-induced amorphization was observed.